2006
DOI: 10.1007/s00220-006-0027-z
|View full text |Cite
|
Sign up to set email alerts
|

Entropy and Quantum Kolmogorov Complexity: A Quantum Brudno’s Theorem

Abstract: In classical information theory, entropy rate and algorithmic complexity per symbol are related by a theorem of Brudno. In this paper, we prove a quantum version of this theorem, connecting the von Neumann entropy rate and two notions of quantum Kolmogorov complexity, both based on the shortest qubit descriptions of qubit strings that, run by a universal quantum Turing machine, reproduce them as outputs.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 48 publications
0
27
0
Order By: Relevance
“…Nevertheless, it has to be stressed that quantum dynamical entropies can be related to the notion of quantum algorithmic complexity, mentioned in section 5, by a quantum version of Brudno theorem established in Ref. [81].…”
Section: Dynamical Entropiesmentioning
confidence: 99%
“…Nevertheless, it has to be stressed that quantum dynamical entropies can be related to the notion of quantum algorithmic complexity, mentioned in section 5, by a quantum version of Brudno theorem established in Ref. [81].…”
Section: Dynamical Entropiesmentioning
confidence: 99%
“…[13] for the classical case and [19] for the quantum case. Also, using f (k) := 1/k as accuracy required on input k is not important; any other computable and strictly decreasing function f that tends to zero for k → ∞ such that f −1 is also computable will give the same result up to an additive constant.…”
Section: Quantum Kolmogorov Complexitymentioning
confidence: 99%
“…In [19], we have shown that for ergodic quantum information sources, emitted states |ψ ∈ C 2 ⊗n have a complexity rate…”
Section: Quantum Kolmogorov Complexitymentioning
confidence: 99%
“…Quantum information theory is a nontrivial generalization of the classical one; hence, one expects that the above arguments can be also generalized that way. Indeed, there are various approaches of quantum information to form the concept of quantum entropy rate [2][3][4][5]. In the present paper, however, we will focus on a description in terms of classical information theory.…”
Section: Introductionmentioning
confidence: 99%